Reduction in depression scores with reminiscence therapy in the elderly: Penurunan skor depresi dengan terapi Kenangan pada lanjut usia - Nurul Husna; Sri Wahyuni (Institute of Educational, Research, and Community Service, 2023)
The aging process that occurs in the elderly brings about physical and psychological changes, leading to deterioration and psychological issues such as depression. Non-pharmacological therapy that nurses can undertake to alleviate depression in the elderly is Reminiscence therapy. This research aims to determine the effectiveness of Reminiscence therapy in reducing depression among the elderly. The research design used is a one-group pre-post test with a sample size of 30 respondents, consisting of 8 males and 22 females. The Geriatric Depression Scale (GDS) questionnaire was utilized. The research findings revealed that the elderly participants were within the age range of 60-65 years (63.3%), predominantly female (73.3%), had a medium level of education (46.7%), were married (76.7%), and had a high income (70.0%). The Wilcoxon test results indicated a significant outcome (p < 0.001) between Reminiscence therapy and depression in the elderly before and after the therapy, with a Mean value before (10.20), SD before (0.805), and Mean value after (7.067), SD (1.946). This therapy can be incorporated into the program of public health centers, particularly for elderly patients experiencing depression, to maintain therapeutic activities